The impact of treatment with indacaterol in patients with COPD: A post-hoc analysis according to GOLD 2011 categories A to D. (June 2015) - Kerstjens, Huib A.M.; Deslée, Gaëtan; Dahl, Ronald; Donohue, James F.; Young, David; Lawrence, David; Kornmann, Oliver
Abstract: Background: Indacaterol is an inhaled, once-daily, ultra-long-acting β2 -agonist for the treatment of chronic obstructive pulmonary disease (COPD). We report on the effectiveness of indacaterol and other bronchodilators compared with placebo in patients across the Global Initiative for Chronic Obstructive Lung Disease (GOLD) 2011 categories A to D. Methods: A post-hoc, subgroup pooled analysis of 6-month efficacy data from three randomized, placebo-controlled, parallel-group studies involving 3862 patients was performed across GOLD 2011 categories A to D, according to baseline forced expiratory volume in 1 s (FEV1 ) % predicted, modified Medical Research Council (mMRC) dyspnea scale, and exacerbation history in the 12 months prior to entry. Efficacy of once-daily indacaterol 150 and 300 μg, open-label tiotropium 18 μg, twice-daily salmeterol 50 μg, and formoterol 12 μg was compared with placebo. End points analysed were trough FEV1, transition dyspnea index (TDI), and St George's Respiratory Questionnaire (SGRQ) total score, all at Week 26, and mean rescue medication use over 26 weeks. Results: Indacaterol 150 and 300 μg significantly improved FEV1, compared with placebo across all GOLD groups. Indacaterol 150 and 300 μg also significantly improved TDI, SGRQ total score, and mean rescue medication use compared with placebo across most GOLD subgroups. Conclusions: Treatment selection according to patient's symptoms as well as lung function is an important consideration in maintenance treatment of COPD. Indacaterol 150 and 300 μg effectively improved lung function and symptoms in patients across all GOLD 2011 categories.